Effect of calcium ions on the adsorption and lubrication behavior of salivary proteins on human tooth enamel surface. (October 2019) - Zeng, Qihang; Zheng, Jing; Yang, Dan; Tang, Yue; Zhou, Zhongrong
Abstract: The aim of this study is to investigate the effect of calcium ions on the adsorption and lubrication behavior of salivary proteins on human tooth enamel. Human whole saliva was collected from healthy donors. Three testing groups were calcium ion-enhanced saliva samples with an increased ion concentration of 1 mmol/L, 5 mmol/L, and 10 mmol/L, respectively. Normal saliva was used as a control. The adsorption behavior was tested using quartz crystal microbalance with dissipation (QCM-D), while the mechanical properties and lubricating behavior of salivary pellicle were examined by nano-indentation/scratch technique. Results show that the increased calcium ion concentration in the saliva weakens the electrostatic interaction between the salivary proteins and enamel surface, but causes increases in the thickness and viscoelasticity of the salivary pellicle formed on enamel surface. Therefore, the load-bearing and anti-shear capacity of the pellicle is improved, and then the anti-wear and friction-reducing effect of the pellicle is enhanced. In sum, the addition of calcium ion in saliva can contribute to the formation of the salivary pellicle with enhanced lubrication performance and help to alleviate the excessive tooth wear of xerostomia patients. Graphical abstract: Image 1 Highlights: Calcium ions strengthen the film-forming properties of salivary proteins. Calcium ions alter the electrostatic bonding of protein-protein and protein-tooth. Calcium ions enhance the pellicle lubrication by raising its load-bearing ability.